Deguelin action involves c-Met and EGFR signaling pathways in triple negative breast cancer cells. - Rajeshwari Mehta (Public Library of Science (PLoS), 2013)
Background Treatment of breast cancer patients with antiestrogens and aromatase inhibitor(s) or Herceptin have shown significant success in steroid receptor positive or Her-2+ breast cancers respectively. However, choice of treatments for breast cancer patients with negative status for estrogen, progesterone receptors and HER2/neu is limited. As a result, search for appropriate therapy regimen for these triple negative breast cancers (TNBC) has become a major focus of investigations for many laboratories. Recently, Deguelin, a natural product isolated from African plant Mundulea sericea (Leguminossae) has shown both antiproliferative actions in various cancers including breast as well as chemoprenventive activity against carcinogen induced experimental cancers. In this report we evaluated efficacy and mechanism of action of Deguelin in triple negative breast cancer cell lines. Methods/findings In vitro, Deguelin in a dose and time dependent manner inhibited the growth of MDA-MB-231, MDA-MB-468, BT-549 and BT-20 cells. Deguelin (2 or 4 mg/kg body weight), when injected intraperitoneally, reduced the in vivo tumor growth of MDA-MB-231 cells transplanted subcutaneously in athymic mice. Moreover it was nontoxic as evident from daily observations on mobility, food and water consumption and comparison of bodyweight and other visceral organ weights with those in control animals at the termination of the study. The western blot analyses and immunostaining studies indicated that the deguelin effects may be mediated through EGFR-PAKT/c-Met p-ERK and NF-κB by down regulating their downstream targets such as p-STAT3, c-Myc, Survivin. Conclusion/significance These results suggest that Deguelin may have a significant therapeutic value for the treatment of TNBC patients.